Feminization Syndrome in a Dog with Sertoli Cell Tumor - Da Silva Flores, Fabiano; Pereira Costa, Eliesse; Inês Ferreira, Priscila; Marchionatti Pigatto, Anita; Cauduro da Rosa, Carolina; Rech Cassanego, Guilherme; Felipe Dutra Côrrea, Luís (Acta Scientiae Veterinariae, 2023)
Background: The uncontrolled multiplication of Sertoli cells causes Sertoli cell tumor or Sertolioma. Because of this, the level of estrogen in the bloodstream increases rapidly and approximately 25% of dogs with this tumor develop feminization syndrome. Testicular neoplasms are more common in dogs than cats, and are often found in elderly patients. This work aims to describe the clinical signs of the feminization syndrome and the treatment instituted in a canine diagnosed with sertolioma. Case: A 18-year-old male canine, 19.5 kg of body mass, with an increase in testicular volume for about 2 years, was treated at the University Veterinary Hospital. On clinical examination, a matte and brittle coat, alopecia on the hind limbs and gynecomastia were observed. Also noted, non-harmonious aspect of the scrotum, pendular foreskin, atrophied right testicle and hyperplastic left, scrotal hyperthermia and absence of pain. In addition, as a result of the hyperestrogenism resulting from the neoplasm, the paraneoplastic syndrome of feminization, the patient also presented galactorrhea, pendular foreskin, atrophy of the penis and the contralateral testicle, dermatopathies, such as bilateral symmetrical alopecia of the flanks, easily removable hair and variable hyperpigmentation. Rectal body temperature of 38.6°C, clear lung auscultation and muffled cardiac auscultation. The results of laboratory tests showed changes such as thrombocytopenia, platelet counts below the reference levels, platelet count of 163,000/uL. There were no alterations that represented metastases in the imaging exams, such as in the chest X-ray in three incidences and in the abdominal ultrasonography. Then, we opted for the surgical procedure of orchiectomy, with the traditional technique of three clamps, associated with total ablation of the scrotum. Samples were sent to the histopathology laboratory and the diagnosis of sertolioma was confirmed. At 10, 30 and 90 days after the operation, the patient was reassessed for possible recurrences or alterations, but there were no complications or recurrence after the procedure. Discussion: Neoplasms of the male reproductive system are common in dogs. Sertolioma is considered one of the most frequent neoplasms in elderly dogs and that results in systemic clinical signs. This is in line with the 18-year-old dog described in the present report. In addition, it may result in clinical signs resulting from hyperestrogenism resulting from the neoplasm that is called paraneoplastic feminization syndrome. The characteristics of this syndrome are: gynecomastia, galactorrhea, pendular foreskin, atrophy of the penis and contralateral testicle, associated with dermatopathies, such as symmetrical bilateral alopecia. All these clinical signs were present. The diagnosis is made through complete anamnesis, complete clinical examination and complementary examination such as ultrasound help in the presumptive diagnosis, but only with histopathology can it be confirmed. In the clinical approach, histopathology was performed to close the diagnosis. Treatment is behind orchiectomy and total ablation of the scrotum, which was performed in the reported case. The treatment of choice was easy to apply, in addition to improving the patient’s quality of life, promoting rapid post-surgical healing and an early return to normal life. However, for the effectiveness of the technique, the early diagnosis and collaboration of tutors is fundamental. Keywords: canine, surgery, neoplasm, orchiectomy. Título: Síndrome da feminilização em cão com sertolioma. Descritores: cão, cirurgia, neoplasia, orquiectomia.